(untitled) - Hoyt, Edwin P. (London, 1986)
This book is for Arleigh Burke, who is famous in postwar Japan as the father of the Self-Defense Forces. As a professional naval officer, Admiral Burke fought the Japanese all during the Pacific War as bravely and hard as he could, and then once victory was in hand, exhibited that compassion for which Americans are justly known and turned about to become one of the best and most effective friends in the world of the New Japan.
Keywords: World War, 1939-1945,World War, 1939-1945,Japan; Campaigns,Politics and government; Pacific area,1868-; Japan